2005: The year of reckoning for Kosovo? - Dušan Reljić (Stiftung Wissenschaft und Politik (SWP), 2005)
A fresh outbreak of armed conflict in and around Kosovo, one that would almost certainly end the fragile stability in many parts of former Yugoslavia, is increasingly becoming an international concern. The question, whether, as announced, negotiations over the province's future status will begin in mid-2005, is still wide open. The ever-louder international debate over Kosovo could lead to renewed friction in the transatlantic relationship, as well as tension between the West and Russia. On 22 February, U.S. President George Bush wants to confer with EU and NATO leaders in Brussels about Kosovo as well as other international security concerns. (SWP Comments / SWP)
Keywords: 320